Public sector pay and adjustment : lessons from five countries - Colclough, Christopher (London ; New York : Routledge, 1997)
Case studies of Singapore, Korea, Zambia, Zimbabwe and Argentina show that in those countries which adjusted unsuccessfully real earnings declined sharply, often with a further negative impact on output.
Book Cover; Title; Contents; Figures and tables; Preface; PUBLIC-SECTOR PAY AND ADJUSTMENT: THEORY, POLICIES AND OUTCOMES; ECONOMIC RESTRUCTURING AND FLEXIBLE CIVIL SERVICE PAY IN SINGAPORE; WAGE POLICY AND INTER-SECTORAL PAY DIFFERENTIALS IN THE REPUBLIC OF KOREA, 1975 91; ECONOMIC STAGNATION AND EARNINGS DECLINE IN ZAMBIA, 1975 91; PUBLIC-SECTOR PAY AND ADJUSTMENT IN ZIMBABWE; STRUCTURAL ADJUSTMENT AND PUBLIC-SECTOR PAY IN ARGENTINA, 1975 91; Index
Includes bibliographical references and index.
Print version record.
eBooks on EBSCOhost
Keywords: Developing countries -- Officials and employees -- Salaries, etc. -- Case studies; Structural adjustment (Economic policy) -- Developing countries -- Case studies; BUSINESS & ECONOMICS -- Labor; POLITICAL SCIENCE -- Labor & Industrial Relations; Employees -- Salaries, etc; Structural adjustment (Economic policy); Developing countries; Ambtenaren; Salarissen; Ontwikkelingslanden; Electronic books; Case studies